Three-dimensional computer modeling of birds proepicardium on different stages of embryogenesis - Pototskaya O.Yu. (Морфологія, 2009)
As the proepicardium is the source of many cell populations of the mature heart, including cell components of coronary vessels, its investigation became actual last time. It is known, that there are some differences between birds and mammalian proepicardium; one of them consists in the way, in which they contact to myocardium: mammalian proepicardium produce vesicles, which contact to atrioventricular groove, wile in birds there is no vesicles and whole protrusions of proepicardium attach to the heart. But, recent years it became evident, that in rat proepicardium there are no vesicles during all stages of its existence, and in birds there is a proepicardium-like structure producing vesicles, which attach to the heart. Thus, the goal of our research was to characterize changes in the shape of proepicardium during bird’s embryogenesis. We used Cobb 500 chick embryos as a material; on the basis of pictures of proepicardium serial sections, with the help of Photoshop CS2, Amira for microscopy 5.0, 3ds max 8.0 computer programs, we made three-dimensional models of proepicardium on 15, 16, 17, 18, 21 stages of development by V.Hamburger, H.Hamilton, 1951. The most important changes in proepicardium shape observed from 14 to 20 stages of development. During this period proepicardium appeared on the right horn of sinus venous, enlarged and formed several crests, which contacted to atrioventricular groove. Coalescence of these crests led to dorsal mesocardium formation. From 21 to 27 stages of development there were no significant changes in proepicardium shape; the area of its contact to sinus venous was grown downwards while the area of contact to the heart enlarged. No vesicles, no “finger-like protrusions” were observed on any stage of bird’s development.